TEACHING LISTENING THROUGH COLLABORATIVE WORK: CAN WE DO IT? - Havid Ardi (Universitas Negeri Padang, 2015)
Listening is one of the skills that should be mastered by any language learners. It usually defines as the ability to identify and understand what others are saying or talking about. However, it is not an easy task. It requires understanding a speaker's accent or pronunciation, his grammar and his vocabulary, and grasping his meaning. Therefore, in teaching listening, teachers need to pay attention on how to help the learner to master this skill. In fact, the way of teaching listening seems to be boring and stressful. The students just sit and listen to the text and fill the blanks or listen to the question. It is merely like a test. This paper aims at sharing the way of teaching listening by using group work or collaborative activities. Listening activities should be challenging and interactive. It must be taught integrated. These activities are aimed at encouraging and facilitating students to take advantage of collaborative activity in order to practice listening skills and communicate and negotiate with others.